MECHANISMS OF STRENGTHENING INVESTMENT AND INNOVATION SECURITY OF UKRAINE IN CRISIS CONDITIONS - BILYK, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the study, attention is updated to the problem of weakening and, accordingly, strengthening the need for the introduction of new mechanisms and instruments of the state policy of strengthening the investment and innovation security of the economy of Ukraine in the conditions of the latest threats caused by the negative consequences of the war.The purpose of the study is to improve the theoretical and methodological foundations and methodological and applied mechanisms of the state policy of strengthening the investment and innovation security of the economy of Ukraine in the conditions of a crisis caused by a full-scale war. It is argued on the low level of investment and innovation security of Ukraine. The indicators of innovative activity in the industry of Ukraine, the indicators of the economy of Ukraine in the rating of the European Innovation Scoreboard in 2023 are characterized. The main indicators of the development of the industrial sector of the economy of Ukraine are given. The results of the analysis of the leading characteristics of the investment and innovation security of the economy of Ukraine are highlighted.It is shown that in order to strengthen the investment and innovation security of the economy of Ukraine, it is necessary to work on overcoming the leading systemic problems that lead to a decrease in the level of investment and innovation security of the national economy of Ukraine. We are talking, firstly, about the deterioration of the investment climate and, secondly, about the lack of effective incentives for the activation of innovative and technological activities.Within the framework of the policy aimed at eliminating the first problem, the leading imperatives of regulation should be: improvement of financial and economic results, increase in the profitability of operational activity and improvement of the financial and economic condition of domestic enterprises of priority types of economic activity; systematic improvement of the investment attractiveness of branches of the national economy; increasing the ability to attract modern innovative technological breakthrough innovations to the economy, etc.Within the policy aimed at improving incentives for the development of innovative and technological activity, it is important to focus on overcoming the disparities between the technological and innovative development of Ukraine and the developed countries of the world; speeding up the pace of structural transformations of the national economic system of Ukraine and its regional socio-economic complexes, etc.It was concluded that the leading mechanisms that should be implemented to strengthen the investment and innovation security of Ukraine's economy in crisis conditions are economic, organizational, institutional, market, infrastructural, and financial and investment.
Keywords: investment and innovation activity; investment and innovation security; strengthening mechanisms; activation; war; crisis; challenges; threats; risks